Determniant Factors of Ovarium Cancer in Abdoel Moelok Hospital Lampung in 2015 - Desi Ari Madi Yanti (Jurnal Keperawatan, 2016)
Ovarian cancer at an early stage does not give complaints, while complaints arise at an advanced stage of cancer because of the spread of cancer, the spread of cancer in serous surface of the colon and ascites is a pain in the abdominal area, uncomfortable and feel full faster. Other symptoms that often arises is easily tired, belly bulge, frequent urination and shortness of breath, so that patients with ovarian cancer will experience a decrease in appetite, decreased activity due to fatigue. The purpose of this study was to determine the relationship determinate factors of ovarian cancer. Design of this study was using analytic with cross sectional approach. The sample in this study were women who were treated in hospital Abdul Moelok at maternity room of 60 people, and measuring using questionnaire and checklist sheet. The results of the study there was no correlation between age and genetic with the incidence of ovarian cancer, and there is a relationship between pads, menarche, menopause and estrogen contraception and the incidence of ovarian cancer. Recommendations researchers are to reduce the use of dioxin pads and estrogen contraception in the long term.